2003
DOI: 10.1046/j.1523-5378.2003.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori and Hepatitis a Virus Infection in School‐Aged Children on Two Isolated Neighborhood Islands in Taiwan

Abstract: Background. The transmission routes of Helicobacter pylori and hepatitis A virus (HAV) infections have been extensively discussed in previous literature. However, whether H. pylori and HAV shared the same transmission pattern or not remains unclear. Lower socioeconomic status was recognized as a consistent risk factor to both infections. However, whether fecal‐oral transmission was a risk factor to both infections is still under debate. Materials and Methods. In 1996, we conducted a cross‐sectional study to ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 38 publications
1
12
1
1
Order By: Relevance
“…Results in this study contrast with prior studies by Chen and others 23 examining a small adolescent population in Taiwan (N = 91), Egemen and others 24 in a sample of children in Izmir, Turkey (N = 102), Lin and others 25 with a sample of primary school students in Taipei (N = 289), and Furuta and others 26 with a clinic-based sample of adults in Japan (N = 1,043). These studies reported weak nonsignificant associations between H. pylori and HAV serology, but were limited in size and scope (all studied non-adult populations, except for Furuta and others) and not generalizable to broader populations.…”
Section: Discussioncontrasting
confidence: 99%
“…Results in this study contrast with prior studies by Chen and others 23 examining a small adolescent population in Taiwan (N = 91), Egemen and others 24 in a sample of children in Izmir, Turkey (N = 102), Lin and others 25 with a sample of primary school students in Taipei (N = 289), and Furuta and others 26 with a clinic-based sample of adults in Japan (N = 1,043). These studies reported weak nonsignificant associations between H. pylori and HAV serology, but were limited in size and scope (all studied non-adult populations, except for Furuta and others) and not generalizable to broader populations.…”
Section: Discussioncontrasting
confidence: 99%
“…The overall prevalence of H. pylori was previously reported to be as high as 54.7z among high school children, significantly higher than the HAV prevalence among children 13-15 years of age (82.4z vs. 5.5z) in Lanyu Island and Green Island, Taiwan (32,46). Recent studies also showed significantly higher prevalence of anti-H. pylori antibodies among teachers compared to children 9-15 years of age (33,47), possibly due to improved socioeconomic and environmental conditions in Taiwan between the 1980s and recent years.…”
Section: Discussionmentioning
confidence: 92%
“…Although some sero-epidemiologic studies reported a common mode of transmission for HAV and H. pylori (46,53,54), another study showed no significant association between H. pylori and HAV seropositivity (28). Because HAV is a sensitive marker of fecal exposure, correlation between HAV and H. pylori seropositivity rates would indicate similar modes of transmission for these 2 pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Although there continues to be debate regarding the H. pylori infection route, the main infection route is thought to be person‐to‐person and frequently within families including children, who can easily get infected [36–39]. Recently, the possibility of oral‐to‐oral infections has been raised instead of fecal to oral [40–42]. If the reinfection is caused by outside source of infection, it might be related with present socioeconomic condition.…”
Section: Discussionmentioning
confidence: 99%